2023
DOI: 10.1097/gox.0000000000004770
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Characteristics of the Ideal Female Breast

Abstract: Background: The female breast is a subject of significant focus within plastic surgery. Little work to date has examined public perceptions of attractiveness with respect to breast anatomy and morphology. This study provides a comprehensive assessment of anatomic and aesthetic breast characteristics valued by the general population. Methods: A single-institution retrospective review was conducted of patients presenting for aesthetic or reconstructive breast surgery between 2009 and 2019. A cohort of 25 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We found no articles directly discussing the topic, several articles that asked black populations to evaluate non-black breasts, 11-13 , 19 and 1 study that evaluated African American breasts as part of an racially heterogenous group of models. 22 Notably, the African American females in this study were found to have relatively curvy and more toned body types coupled with large upper poles, substantial UPS convexity, and larger areolas when compared with the Caucasian females. Anecdotally, African American patients often place heavy importance on maintaining a curvaceous figure, which is consistent with their preference for curvier back and buttock aesthetics.…”
Section: Discussionmentioning
confidence: 55%
“…We found no articles directly discussing the topic, several articles that asked black populations to evaluate non-black breasts, 11-13 , 19 and 1 study that evaluated African American breasts as part of an racially heterogenous group of models. 22 Notably, the African American females in this study were found to have relatively curvy and more toned body types coupled with large upper poles, substantial UPS convexity, and larger areolas when compared with the Caucasian females. Anecdotally, African American patients often place heavy importance on maintaining a curvaceous figure, which is consistent with their preference for curvier back and buttock aesthetics.…”
Section: Discussionmentioning
confidence: 55%
“…A survey conducted by Bekisz et al in 2023, collected 1021 responses from a diverse population. 118 The primary objective of the study was to evaluate the aesthetic and anatomical characteristics valued by patients seeking ABS. According to this study, females generally preferred “moderate”-sized breasts with a greater upper pole fullness to lower pole ratio.…”
Section: Discussionmentioning
confidence: 99%